Optoelectronic reciprocity in hot carrier solar cells with ideal energy selective contacts. (10th January 2021) - Pusch, Andreas; Dubajic, Milos; Nielsen, Michael P.; Conibeer, Gavin J.; Bremner, Stephen P.; Ekins‐Daukes, Nicholas J.
Abstract: Hot carrier solar cells promise theoretical power conversion efficiencies far beyond the single junction limit. However, practical implementations of hot carrier solar cells have lagged far behind those theoretical predictions. Reciprocity relations for electroluminescence from conventional single junction solar cells have been extremely helpful in driving their efficiency ever closer to the theoretical limits. In this work, we discuss how the signatures of a functioning hot carrier device should manifest experimentally when driven in reverse, that is, in electroluminescent mode. Hot carrier properties lead to deviations of the dark I–V from the Shockley diode equation that is typical for conventional single junction solar cells. These deviations are directly linked to an increase in temperature of the carriers and therefore the temperature measured from electroluminescence spectra. We also elucidate how the behaviour of hot carrier solar cells in the dark depends on whether Auger processes play a significant role, revealing a stark contrast between the regime of negligible Auger recombination (carrier conservation model) and dominant Auger recombination (impact ionisation model) for hot carrier solar cells. Abstract : Optoelectronic reciprocity dictates that signatures of a functioning hot carrier device should manifest experimentally in electro‐luminescence and dark I‐V characteristics. Hot carrier properties, observable from electro‐luminescence spectra are directly linked to deviations from exponential behaviour in the dark I‐V. The behaviour of hot carrier solar cells in the dark depends on whether Auger processes play a significant role, revealing a stark contrast between the regime of negligible Auger recombination (large bandgap) and dominant Auger recombination (vanishing or small bandgap).